A Hedonic Analysis of Processed Tomato Prices Using Italian Regional Markets Data - Emilio De Meo; Gianluca Nardone; Francesco Bimbo; Domenico Carlucci (Foods, 2022)
The Italian market of processed tomatoes (whole peeled and unpeeled tomatoes, chopped tomato pulp, tomato purée, and concentrated tomato paste) rose, thanks to the Italian tradition of using such products in many recipes of cuisine, until early 2000; since then, it has declined to date. Moreover, such products are traditionally considered low-price products, and their market is characterized by intense price competition. Thus, recently, producers have started to differentiate their products as a way to achieve higher margins, and escape from competition in price. By using the sales data of Italian processed tomatoes sold in several retail stores and a hedonic price model, we estimated the implicit prices associated with several attributes that are currently available in processed tomato products on the market. We find that a protected designation of origin, organic certification, and flavoring, as well as the indication of tomato variety, are the most valuable features of processed tomato products sold in the Italian market. This implies that product differentiation strategies that could be suggested to producers as the most effective are those aimed at enhancing the territorial link of the product, the environmental sustainability of the production process, and organoleptic product features, as well as its convenience.